Involvement of cyclic GMP in intracellular signaling in the chemotactic response of Escherichia coli. - Black, R A (1980)
The intracellular signal that produces changes in swimming behavior when bacteria encounter attractants or repellents has not previously been identified. We suggest, based on the following lines of evidence, that cyclic GMP (cGMP) is involved in this signaling process in chemotaxis by Escherichia coli. (i) The addition of attractants to bacteria causes a transient increase in the intracellular level of cGMP, whereas a repellent stimulus decreases the level transiently. These changes do not generally occur in a mutant lacking chemotaxis-specific proteins. (ii) In the absence of chemoeffectors, both addition of cGMP to bacteria and reducing the intracellular cGMP level produce changes in swimming behavior, and a mutant with an abnormal swimming pattern has an altered intracellular cGMP level. (iii) cGMP modulates the demethylation reaction responsible for adaptation to stimuli. (iv) Mutants defective in components of the adaptation system have altered cGMP metabolism.